The Politics of Economic Change in Postwar Japan and West Germany
IX, 375 p.
Keywords: The book begins with an editors' introduction that provides a conceptual setting for a comparative study of the role of policy in the development of the postwar Japanese and West German economies. It then offers detailed comparative analyses of developments in the two countries on seven substantive topics: an overview of macroeconomic change; economic advisory and planning; monetary control; inflation control; labour markets and wage determination; agriculture and social security and welfare. It ends with an editor's summary and conclusion.